Risk factors for anastomotic leakage and postoperative outcomes after total and subtotal colectomy: A nationwide retrospective cohort study (RIALTCOT Study Collaborative Group). (9th November 2022) - Ocaña, Juan; Pastor, Paula; Timoteo, Ander; Diez‐Alonso, Manuel Mariano; de la Portilla, Fernando; Cagigas, Carmen; Labalde‐Martínez, María; Espin, Eloy; Dujovne, Paula; Nieto, Marta; González, Manuel; Sanz, Rodrigo; et al.
Abstract: Aim: Anastomotic leakage (AL) following ileorectal (IRA) or ileosigmoid (ISA) anastomosis is associated with a high morbidity. The identification of potential risk factors for AL could change operative planning and reduce further complications. This study assesses the rate, potential risk factors and management of AL after total colectomy (TC) and subtotal colectomy (STC). Methods: A nationwide, multicentre, retrospective cohort study involved 26 Spanish referral centres. It included TC and STC with IRA or ISA patients between January 2013 and December 2020. Clinical data, primary surgery and complications were collected. Univariate and multivariate analysis to identify risk factors for AL were performed. Management of Grade B–C AL and permanent stoma rate was assessed according to revisional surgeries. Results: The study included 1074 patients, 433 ISA group (40.3%) and 641 IRA group (59.7%). The overall incidence of AL was 14.3% with no differences between IRA and ISA (14.2% and 14.5% respectively), P = 0.871. Male sex, ASA score and lower total preoperative proteins were identified as independent risk factors for global and Grade B–C AL. Diverting ileostomy did not protect against AL ( P = 0.084). Clavien–Dindo ≥IIIA complication was found in 251 patients (23.3%). Stoma reversal was not possible in 85 patients (8.1%), being more frequent after anastomosis excision and terminal ileostomy in AL Grade C. Conclusion: Total colectomy and STC with IRA or ISA are high‐risk procedures with an increased AL rate. Male sex, ASA score and lower preoperative protein level were associated with global AL and AL Grade B and C. A lower permanent stoma rate could be obtained when diverting ileostomy is performed in revision surgery.